Pengaruh Latihan Metode Drill Dan Power Tungkai Terhadap Akurasi Shooting Pada Klub Futsal di SMAN 1 Kota Gorontalo - Madu, Rahmat Safitra; Raharjo, Hermawan Pamot; Raharjo, Agus (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aimed to analyze the extent of drill and leg power training methods on shooting accuracy at the futsal club at SMAN 1 Gorontalo City. The technique used in this research uses a quantitative approach with a 2x2 factorial research design. The data collection technique was carried out using a shooting accuracy test to see the differences before and after treatment (pretest-post test). The population of futsal athletes at SMAN 1 Gorontalo City totals 20 athletes. The sampling technique in this study was purpose sampling by setting specific criteria (leg power), and the sample that fell within the criteria was 16 athletes. The results of this study show that there is a significant difference in values ​​in the straight-running one-touch shooting drill exercise between fixed repetitions, changing sets with changing repetitions, and fixed sets with a Sig p-value of 0.008 < 0.050; there is a difference in the influence of leg power and shooting accuracy, with a Sig p-value of 0.002 < 0.050; There is an interaction between leg power and one-touch shooting straight running training, fixed repetitions, changing sets 0.007 < 0.050; There was an interaction between high leg power and one-touch shooting straight running training, changing repetition groups, fixed sets on shooting accuracy 0.039 < 0.050; There is an interaction between low leg power and straight running one touch shooting training in fixed repetition groups, changing sets on shooting accuracy. 0.026 < 0.050; There was no interaction between low leg power trained using straight running touch shooting training, changing repetition groups, and fixed sets on shooting accuracy. 0.139 > 0.050. In conclusion, the straight running drill training method of one-touch shooting between fixed repetitions, changing sets with changing repetitions, fixed sets, and low and high leg power greatly influences shooting accuracy. Keyword: Drill Method Training, Futsal, Limb Power